The Influence of Problem Based Learning on Students’ Creative Thinking Skills on Earth and Solar System Topic - Awinda, Awinda; Fadilah, Muhyiatul; Yurnetti, Yurnetti; Evita Putri, Rahmah (SEMESTA: Journal of Science Education and Teaching, 2025)
Students at SMPN 1 Kecamatan Guguak currently demonstrate low creative thinking skills. This study aims to investigate the effect of the Problem-Based Learning (PBL) model on improving creative thinking skills among seventh-grade students in the topic of Earth and the Solar System. The research employed a quasi-experimental method with a posttest-only control group design. The population consisted of all seventh-grade students at SMPN 1 Kecamatan Guguak, while the sample included two classes—an experimental class and a control class—selected through purposive sampling. The criteria of this sampling technique are similarities in average class scores, teacher who teaches, and schedule. Primary data were collected from students’ creative thinking skill scores by using test consisted of eight questions. The test refers to Guilford's creative thinking indicators, namely fluency, flexibility, originality, and elaboration. The data were analyzed using an independent sample t-test. The results of the analysis showed a significance value of 0.001 < 0.05, indicating that the implementation of the PBL model significantly improved students’ creative thinking skills.